Assessing Bladder Radiotherapy Response With Quantitative Diffusion-Weighted Magnetic Resonance Imaging Analysis. Issue 10 (October 2022) - Hafeez, S.; Koh, M.; Jones, K.; El Ghzal, A.; D'Arcy, J.; Kumar, P.; Khoo, V.; Lalondrelle, S.; McDonald, F.; Thompson, A.; Scurr, E.; Sohaib, A.; et al.
Abstract: Aims: Radiotherapy with radiosensitisation offers opportunity for cure with organ preservation in muscle-invasive bladder cancer (MIBC). Treatment response assessment and follow-up are reliant on regular endoscopic evaluation of the retained bladder. In this study we aim to determine the role of diffusion-weighted magnetic resonance imaging (DWI) and apparent diffusion coefficient (ADC) analysis to assess bladder radiotherapy response. Materials and methods: Patients with T2-T4aN0-3M0 MIBC suitable for radical radiotherapy were recruited prospectively to an ethics approved protocol. Following transurethral resection of the bladder tumour and prior to any treatment, magnetic resonance imaging including DWI was performed on a 1.5T system using b values of 0, 100, 150, 250, 500, 750 s/mm 2 . DWI was repeated 3 months after completing radiotherapy. Cystoscopy and tumour site biopsy were undertaken following this. The response was dichotomised into response (<T2) or poor response (≥T2). Tumour region of interest was delineated on b750 s/mm 2 image and transferred to the ADC map to calculate per pixel ADC values for all b values (ADCall ) and high b values (ADCb100 ). ADC mean, percentiles, skew, kurtosis and their change (ΔADC and %ΔADC) were determined. Threshold predictive of response with highest specificity was ascertained using receiver operating characteristic analysis. Results: Thirty-four patients were evaluated. Response was associated with a significant increase in ΔADC mean compared with poor response at ΔADCall (0.57 × 10 −3 mm 2 /s versus –0.01 × 10 −3 mm 2 /s; P < 0.0001) and ΔADCb100 (0.58 × 10 −3 mm 2 /s versus –0.10 x 10 −3 mm 2 /s; P = 0.007). A 48.50% increase in %ΔADCall mean was seen in response compared with a 1.37% decrease in poor response ( P < 0.0001). This corresponded to a %ΔADCb100 mean increase of 50.34% in response versus a 7.36% decrease for poor response ( P < 0.0001). Significant area under the curve (AUC) values predictive of radiotherapy response were identified at ΔADC and %ΔADC for ADCall and ADCb100 mean, 10th, 25th, 50th, 75th and 90th percentiles (AUC >0.9, P < 0.01). ΔADCall mean of 0.16 × 10 −3 mm 2 /s and ΔADCb100 mean 0.12 × 10 −3 mm 2 /s predicted radiotherapy response with sensitivity/specificity/positive predictive value/negative predictive value of 92.9%/100.0%/100.0%/75.0% and 89.3%/100.0%/100.0%/66.7%, respectively. Conclusions: Quantitative DWI analysis can successfully provide non-invasive assessment of bladder radiotherapy response. Multicentre validation is required before prospective testing to inform MIBC radiotherapy follow-up schedules and decision making. Highlights: Quantitative diffusion-weighted MRI analysis to assess bladder radiotherapy response is feasible. Significant increase in measured ADC characteristics is seen in those who achieve response compared with poor response. It provides prognostic information that may help risk-stratify patients and personalise future follow-up. Multicentre validation to assess reproducibility and repeatability is required before prospective testing.